Mengapa Saya Tidak Asertif? Tinjauan Asertifitas Dari Konsep Diri Dan Ketidakhadiran Ayah Pada Remaja Yang Mengalami Bullying - Sasqia Desta, Safitri; Fitriani, Annisa; Salsabila, Mustamira Sofa (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2024)
Adolescence is a phase where individuals have more ability demands than previous phases in behaving and acting towards themselves. Good assertiveness will form a positive self-concept. If the father's role is not found in instilling assertiveness, then teenagers tend not to be able to communicate well and this makes it difficult for them to resist bullying behavior. This research aims to determine the relationship between self-concept and fatherless and assertiveness in adolescents who experience bullying. The population in this study was teenagers aged 13 – 18 years. This research is quantitative research with data collection methods using the theoretical assertiveness scale Alberti & Emmons (2017) which was adapted from (Asysyura & Rizal, 2020). The theoretical self-concept scale Berzonsky (1981) is an adaptation of the scale Hadziqoh et al., (2023) and the fatherless theory scale Smith et al., (2017) which is adapted from the scale (Zulkarnaini & Rahma Nio, 2023). Data analysis used multiple regression analysis with the help of JASP 0.18.1 software. The results of the research show that the coefficient of determination (r2) = 0.443 with (p<0.001), so it can be concluded that self-concept and fatherless have an influence on assertiveness of 44.3%. It can be concluded that the hypothesis is accepted. Keywords: Assertiveness; Self-concep; Fatherless